1979
DOI: 10.1073/pnas.76.12.6661
|View full text |Cite
|
Sign up to set email alerts
|

Induction of maternal behavior in virgin rats after intracerebroventricular administration of oxytocin

Abstract: Oxytocin produces uterine contractions and milk ejection, functions related to parturition and nurturing. Studies were conducted to determine if this peptide, native to the brain and the posterior pituitary gland, plays a role in the induction of maternal behavior. Intact virgin female rats were given 0.4 ,g of oxytocin, 0.4 1&g of [Arg8Jvasopressin, or saline through lateral ventricular cannulae. Forty-two percent of intact rats receiving oxytocin displayed full maternal behavior towards foster pu s. None of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
363
1
7

Year Published

1982
1982
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 697 publications
(380 citation statements)
references
References 35 publications
9
363
1
7
Order By: Relevance
“…Finally, OT and AVP were known to be important for the bond between mother and offspring. Indeed, central administration of OT has been found to enhance maternal behavior in sheep (Kendrick et al, 1987) and rats (Pederson et al, 1979).…”
Section: Neuropeptidergic Regulation Of Social Attachmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, OT and AVP were known to be important for the bond between mother and offspring. Indeed, central administration of OT has been found to enhance maternal behavior in sheep (Kendrick et al, 1987) and rats (Pederson et al, 1979).…”
Section: Neuropeptidergic Regulation Of Social Attachmentmentioning
confidence: 99%
“…This pairing of sex with peptide was probably chosen because of the known sexual dimorphism and testosterone sensitivity of the BNST-LS AVP pathway and involvement of OT in mother-infant bonding (Pederson et al, 1979;De Vries et al, 1983;Kendrick et al, 1987;De Vries et al, 1990;Kendrick et al, 1992). Thus, AVP and OT were thought to have gender specific effects; AVP regulating pair bonding in male prairie voles and OT regulating the same behavior in female prairie voles Williams et al, 1994;Insel et al, 1995a).…”
Section: Neuropeptidergic Regulation Of Social Attachmentmentioning
confidence: 99%
“…A review of some of the evidence for neurochemical control of vocalizations in anxiety-provoking circumstances has been presented by Newman [72]. In addition, the neuropeptides vasopressin (AVP) and oxytocin (OT) have attracted a lot of interest, due to the evidence that they are involved in regulating social attachment behavior in rodents and non-human primates [39,41,42,49,70,92,120,121].…”
Section: Neurochemical Control Of Cryingmentioning
confidence: 99%
“…Saline-or vasopressin-treated animals showed no maternal behavior. The oxytocin-induced maternal behavior was facilitated by concomitant administration of estradiol benzoate, to simulate the hormonal status of females in estrus [92]. Oxytocin in the nucleus accumbens has been associated with parental vigor in caring for pups in the prairie vole [85].…”
Section: Neurochemistry Of Cry Perceptionmentioning
confidence: 99%
“…The first evidence that oxytocin influences behavior came in the 1980s, when Cort Pedersen and colleagues reported that oxytocin induces the onset of maternal behavior in virgin rats (Pedersen and Prange, 1979), and Kendrick et al (1997) showed that oxytocin stimulates the mother-infant bond in sheep. A series of papers published in the 1990s using monogamous prairie voles as subjects showed that oxytocin also stimulates pair bonding (reviewed in Ross and Young, 2009).…”
mentioning
confidence: 99%